An engineering modification to the blade element momentum method for floating wind turbines. Issue 4 (1st May 2022) - Mancini, Simone; Boorsma, Koen; Caboni, Marco; Hermans, Koen; Savenije, Feike
Abstract: The design of next-generation offshore wind rotors for floating applications carries large uncertainties that make it harder to bring costs down. A significant share of this uncertainty is associated with the use of Blade Element Momentum (BEM) methods to run aeroelastic design and loadcase calculations, because the assumptions underlying the momentum theory are violated by the floater motion. This work presents an engineering method for BEM that allows to model generic floater motions and improves the aerodynamic modelling of floating wind turbines. The new model overcomes the challenge of estimating the apparent wind caused by the platform motion in a simple way, which proves to be very effective for rigid aerodynamic simulations. To verify its impact, BEM results with and without the proposed correction are compared to high-fidelity free vortex wake simulations, imposing the same harmonic motion first to the pitch and then to the yaw degree of freedom of the platform. While little differences are found for the yaw motion, the new floating model clearly improves predictions for the platform pitch case in terms of both aerodynamic loads and induction, finding a very good match with the high-fidelity results. An analysis of the verification data provides new valuable insights on the effect of these motions on aerodynamic loads and performance of a floating wind turbine.